2019
DOI: 10.1021/acsomega.9b02203
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Stability Studies of Ge-Based Perovskites of Controllable Mixed Cation Composition, Produced with an Ambient Surfactant-Free Approach

Abstract: In this report, we have applied a facile, ligand-free, ambient synthesis protocol toward the fabrication of not only a series of lead-free Ge-based perovskites with the general formulation of MA1–xFAxGeI3 (where x was changed from 0, 0.25, 0.5, 0.75, to 1) but also CsGeI3. Specifically, our methodology for producing ABX3 systems is generalizable, regardless of the identity of either the A site cation or the X site halide ion. Moreover, it incorporates many advantages, including (i) the possibility of efficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 37 publications
2
33
0
Order By: Relevance
“…5, the authors devised a simple synthetic procedure modifying and adapting traditional ligand-assisted reprecipitation method for Pb-based perovskite synthesis, thus avoiding the use of concentrated HI and H 3 PO 2 . [8] X-ray Diffraction (XRD) study of the prepared samples confirmed phase pure materials with a progressive increase of the trigonal unit cell by increasing the amount of bigger FA. Scanning Electron Microscopy (SEM) yielded composition-dependent morphologies in terms of size and shape and representative images for MAGeI3 and FAGeI3 are reported in Figure 1b and 1c, respectively.…”
Section: D Perovskitesmentioning
confidence: 86%
See 4 more Smart Citations
“…5, the authors devised a simple synthetic procedure modifying and adapting traditional ligand-assisted reprecipitation method for Pb-based perovskite synthesis, thus avoiding the use of concentrated HI and H 3 PO 2 . [8] X-ray Diffraction (XRD) study of the prepared samples confirmed phase pure materials with a progressive increase of the trigonal unit cell by increasing the amount of bigger FA. Scanning Electron Microscopy (SEM) yielded composition-dependent morphologies in terms of size and shape and representative images for MAGeI3 and FAGeI3 are reported in Figure 1b and 1c, respectively.…”
Section: D Perovskitesmentioning
confidence: 86%
“…Noteworthy, the recent emergence of chiral perovskites as suitable materials for nonlinear optical properties, among which SHG response, could be further explored by considering Ge-containing systems. [7] More recently, the MA1-xFAxGeI3 (x = 0, 0.25, 0.5, 0.75, 1) solid solution was systematically investigated by Yue et al [8] Differently from ref. 5, the authors devised a simple synthetic procedure modifying and adapting traditional ligand-assisted reprecipitation method for Pb-based perovskite synthesis, thus avoiding the use of concentrated HI and H 3 PO 2 .…”
Section: D Perovskitesmentioning
confidence: 99%
See 3 more Smart Citations